Isolation and Identification of Indigenous Plastic-Degrading Bacteria from Dumai’s Ocean Water of Riau Province - Mardalisa Mardalisa; Eza Buana Fatwa; Dessy Yoswaty; Feliatra Feliatra; Irwan Effendi; Bintal Amin (Ilmu Perairan (Aquatic Science), 2021)
One of the interesting and environmentally friendly microbiology strategies and approaches to control the impact of microplastics is to approach bioremediation technology by harnessing the potential of microbes or indigenous bacteria (local bacteria).  Dumai sea waters currently show a high enough of microplastic pollution which allows the potential of indigenous bacteria to adapt to a plastic environment. The purpose of this study is to isolate and identify indigenous bacteria to degrade plastics from the sea waters of Dumai and to know whether or not there is a difference in the number of bacteria found between stations in this study. This research was conducted in October-December 2020 with experimental methods at the Marine Microbiology Laboratory Faculty of Fisheries and Marine Science Universitas Riau. Based on the results of the study, 12 bacterial isolates were isolated from the research stations.  Isolates of these bacteria have diamaters ranging from 0.2-1.1 cm. Microplastic degradation test results by bacteria found that ISL 10 is an isolate that shows the highest PET degradation activity, which is 17.27% and the diameter of biofilm formation 0.8 cm. Based on biochemical and morphological tests, similar results were obtained that ISL 10 bacteria are a bacterium of the genus Bacillus. The most bacterial colonies were seen in statiun IV (TPI) with an average number of bacteria of 214.9 x 104 CFU/ml.